The effectiveness of Emotion-Focused Therapy on Reducing Anxiety and Self-Compassion in Adolescents - Minaei, Hosein (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to evaluate the effectiveness of Emotion-Focused Therapy on reducing anxiety and self-compassion in adolescents aged 14 to 19 years 2021. Methods: The method of the present study is quasi-experimental and a pre-test-post-test design with a control group has been used to collect data. The statistical population of the study consisted of all female students aged 14 to 19 years from Shahid Beheshti Girls’ High School in Tehran among them, 30 people were selected by available sampling method and randomly assigned to the experimental group (15 people in each group) and control group (15 people). The experimental group Emotion-Focused Therapy underwent 8 sessions of 90 minutes and the control group remained on the waiting list. The instruments used in the present study included the Anxiety Inventory (Beck, 1996) and the Self-Compassion Questionnaire (Nef, 2003), which were used in two stages: pre-test and post-test. The analysis of the information obtained from the questionnaire was performed through spss24 software in two descriptive and inferential sections (analysis of covariance). Results: The results showed that emotion-oriented therapy decreased anxiety (F=21.02, P=0.001) and increased self-compassion (F=138.47, P=0.001) in the post-test phase and this effect in the phase the follow-up was stable. Conclusion: According to the results of this study, emotion- Focused therapy is an effective intervention in reducing anxiety and increasing self-compassion in students.